Rancang Bangun Game 2D Shooter Menggunakan Metode Finite State Machine - Nopriansyah, Agung; Kanedi, Indra; Prahasti, Prahasti (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This 2D Shooter game is an adventure video game where the player plays the character of a Survivor. This game focuses on the Survivor's adventure to kill all the monsters in order to continue to the next level until the end. This game uses the Unity game engine, by implementing the Finite State Machine. Finite State Machine is used on NPCs (Non-Playable Characters), namely characters that appear in the game as monsters in the game such as Enemy and Boss characters.In the tests that have been carried out the results of the FSM (Finite State Machine) in this 2D Shooter game, most of the respondents with an average of 32% answered Very Good, 41% answered Good, 24% answered Moderate, 3% answered Poor.